Ethical Standards in Sport and Exercise Science Research: 2020 Update - Harriss, D. J.; MacSween, A.; Atkinson, G. (International Journal of Sports Medicine, 2019)
For publication in the International Journal of Sports Medicine (IJSM), studies must have been conducted in accordance with recognised ethical standards and national/international laws. At the very first stage of paper submission, authors are required to confirm that these standards and laws have been adhered to by reading this editorial. Authors who do not provide any information regarding ethical approval will have their manuscripts rejected before it enters the peer-review process, without any option to resubmit.